Metagenomic insights into pathogenic bacteria and antimicrobial resistance in offshore coastal sediments – An example from Gulf waters - Nazima Habibi; Saif Uddin; Hanan Al Sarawi; Ahmad Aldhameer; Montaha Behbehani; Saja Fakhraldeen; Waleed Al-Zekri; Nasreem Abdulrazzack; Farhana Zakir; Anisha Shajan (Environmental Challenges)
The environment-mediated spread of antimicrobial resistance (AMR) has become a serious public health issue. Globally, indiscriminate waste discharges in marine environments are one of the key contributors to pathogenic bacteria, antibiotic resistance genes (ARGs), and mobile genetic elements (MGEs). In this communication, we report the presence of 192 known bacterial pathogens at sites 3–40 km away from the coast of Kuwait. Pseudomonas aeruginosa was the most dominant species, recording a relative abundance of 88 % even at remote sites. Other pathogens, such as Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumonia, Acinetobacter baumannii, Enterobacter cloacae, and Escherichia coli, prioritised by the World Health Organization (WHO) were also recorded. The raw sequencing reads matched with 667 ARGs, 1606 plasmids, 167 integrons and 2143 insertion sequences. The ARGs exhibited spatial variations and were distributed into three overlapping clusters (r2 = 0.277; p < 0.006). The observed Shannon and Simpson indices differed between the groups (ANOVA-p < 0.05). A positive correlation (R2–0.175, p < 0.065) between faecal sterols and ARGs was recorded. The presence of ARGs in non-polluted sites likely suggests that they are not restricted to waste outlets; it is quite probable that other emerging contaminants are also leading to AMR occurrence in the region. Hence, comprehensive screening and constant surveillance are warranted.